Pull-out and bond-slip performance of steel fibers with various ends shapes embedded in polymer-modified concrete. (15th February 2021) - Esmaeili, Jamshid; Andalibi, Keyvan; Gencel, Osman; Maleki, Farshid Khosravi; Maleki, Vahid Arab
Highlights: Impact of geometric shape of fiber ends and fiber diameter were studied. Impact of diameter and hook angle on bond characteristics of fibers was also studied. Pull-out performance of steel fibers in polymer based concrete was determined. Interaction among fibers and polymer composite is predicted. Experimental test results were compared with finite element method. Abstract: The bond-slip behavior between matrix and fibers highly depends on the geometric and mechanical characteristics of fibers. Thus, by considering various geometric of fiber end shapes, the pull-out behavior of steel fibers from polymer-modified concrete is studied in the present study. For that, a three-dimensional non-linear finite element method is employed for simulations. For considering more real guess, interaction among matrix and fibers is simulated via Interfacial Transition Zone (ITZ), and its factors are attained from experimental results of the fiber pull-out test. After validating the results, the effect of geometric parameters of the fibers end shape on the bond-slip properties with polymer composite is investigated. The results from the load-slip curves indicate that there are different mechanisms in the behavior of the fibers depending on the diameter and angle of the fibers. For fibers with 2 mm diameter, increasing the angle of the hook from 0 to 90 degrees increases the pull-out force of hook and half-hook fibers by about 35% and 15%, respectively. Whereas a further increase in hook angle reduces pull-out parameters of the hook-shaped fibers.